Analisis Tingkat Motivasi Belajar Mahasiswa dalam Perkuliahan - Yulianti, Heni; Handini, Handini; Pebrianti, Alpina; Gunawan, Gunawan (Indonesian Journal of Social Sciences and Humanities, 2026)
Learning motivation is a key factor influencing student success in the lecture process. Understanding the level of learning motivation is necessary to help universities design more effective learning strategies. Therefore, this study was conducted to obtain an overview of the state of student learning motivation during the lecture process. This study aimed to measure the level of student learning motivation and identify the factors that influence it. This survey also aimed to provide a basis for developing learning recommendations that can increase student participation and engagement. The research method used was a descriptive survey involving all respondents who participated in filling out the questionnaire, so that the entire survey population served as the research data source. The instrument used was an online questionnaire containing indicators of intrinsic motivation, extrinsic motivation, learning interest, and student perceptions of the lecture process. The results showed that the level of student learning motivation was in the moderate to high category, with intrinsic motivation being the most dominant component. Factors that most influenced learning motivation included interest in the course, the lecturer's teaching methods, and a supportive learning environment. Furthermore, it was found that students with good learning interactions had higher learning motivation than those who were less involved in class discussions. In conclusion, student learning motivation during lectures is influenced by a combination of internal and external factors. These findings can serve as a basis for developing more adaptive, interactive, and student-centered learning strategies to improve motivation and overall learning outcomes.